Contextual effects of socioeconomic level on academic achievement in obligatory secondary education in the Basque Autonomous Community (Spain). Differential study about socioeconomic level of families and school centers. - Lizasoain, Luis; Joaristi, Luis; Lukas, José Francisco; Santiago, Karlos (Education Policy Analysis Archives, 2007)
The aim of this paper is to analyze the contextual effect of the socioeconomic status (SES) on the academic achievement in Mathematics and Language in Compulsory Secondary Education at the Basque Autonomous Community (Spain). We have carried out a differential study taking into account family SES and school SES in a multi-level study context. First, via tested hierarchical models, the hypothesis of the contextual effects (i.e., double jeopardy) is accepted, showing that the academic achievement of students from low SES families tend to worsen when they attend low SES schools. In order to illustrate the different effect of both SES, a new variable is generated so that, for each student, it combines the values of the previously categorized family and school SES. Using statistical segmentation techniques (regression and classification trees, CART), the present study has found that low family SES students attending high SES schools obtain the best academic achievement results, only outperformed by high family SES students who are studying at high SES schools, and also, even better than the sample subgroups who were expected to get much better scores. The study ends with some explanatory hypotheses about the findings and with some suggestions for further research.